(3eYjf GdWdGH Ydi Yed GdCSWQdGH (B( (3hGdQNGeI hGdWGSI (B)s - (3YeQ Hf jhSa Hf YeQ Hf Ydj Hf QShd, CHh MaU, eegO GdOjf, Gdedc GdCTQa,J (B696 (3g` s
(3ChdgG (B:s
(3jbhd hHYO adeG cGf GdGSWQdGH GTQa Bdg hVYJ ai Yde Gdadc GMHHJ Cf GLeY ai Ydeg QSGdI ehVMI bjHI GdeSdc HWQjbI eUMMI s
(3BNQgG (B:s
(3hjSJeQ Edi BNQ NW GdJbSje GdPi YfO NW hSW GdSeGA hgh g`n hbO ced GdLeY hEdi gGgfG GfJgi GdcdGe JeJ GdQSGFd s
(3HgG QShe hLOGhd YOjOIs
(3HChdgG Jedc OGhO CNj GdeDda hHBNQgG ELGRJGf ef eYdei GdeDda GHQGgje Hf eeOhO GdLdGO GdehUdi GdMGSH SfI (B690 (3hMSf Hf Ydi GdagQi GdeXaQi GdGTQai (B692 (3dYOI GSWQdGHGJ UfYgG Gds
(3cJHJ gPg GdfSNI Hbde ajg VHW GdfbW CMjGfkGs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
Keywords: (3Gdadcs